1986
DOI: 10.1128/jcm.24.1.104-107.1986
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Staphylococcus epidermidis growth in peritoneal dialysis solutions

Abstract: Staphylococcus epidermidis is the most frequent cause of peritonitis complicating continuous ambulatory peritoneal dialysis. We studied factors that might influence the growth of S. epidermidis in commercially available peritoneal dialysis solution (PDS). Test strains were inoculated into PDS and incubated overnight at 37°C. Samples were removed at appropriate intervals, bacterial counts were performed, and growth curves were constructed. We studied the effects of various osmolarities, the neutralization and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 15 publications
(11 reference statements)
2
10
0
Order By: Relevance
“…It was shown in previous studies that S. epidermidis grows best in slightly more acidic pH close to around 6.35 but demonstrates the ability to growth in a range of pHs [30] [31]. In this study S. epidermidis seemed to be resistant to alkali pH due to the effects of magnesium, as revealed by the increase in the bacterial number up to 72 h for all samples tested.…”
Section: Discussionsupporting
confidence: 56%
“…It was shown in previous studies that S. epidermidis grows best in slightly more acidic pH close to around 6.35 but demonstrates the ability to growth in a range of pHs [30] [31]. In this study S. epidermidis seemed to be resistant to alkali pH due to the effects of magnesium, as revealed by the increase in the bacterial number up to 72 h for all samples tested.…”
Section: Discussionsupporting
confidence: 56%
“…It is well known that isolates from CAPD patients with peritonitis often grow poorly or not at all in the fresh acidic dialysis fluid that is instilled into the peritoneal cavity (11,14). Furthermore, the composition of this fluid changes rapidly during dialysis, and so many workers have instead used PUD as a culture medium (8)(9)(10)(11)(12)(13)(14)16). The pH of PUD quoted in these references ranged from 7.0 to 8.6.…”
Section: Discussionmentioning
confidence: 99%
“…fluid represents a step closer to these conditions. The peritoneal cavities of patients undergoing continuous ambulatory peritoneal dialysis (CAPD) represent a unique growth environment for potential pathogens, and therefore in vitro studies of peritonitis-causing isolates have employed used peritoneal dialysis fluid (PUD) as a culture medium (8)(9)(10)(11)(12)(13)(14)16). In addition to differences in growth kinetics, we have shown unique phenotypic changes in staphylococcal cell surface characteristics associated with growth in PUD (17,19; S. P. Denyer, M. C. Davies, J.…”
mentioning
confidence: 99%
“…The principal pathogens associated with CAPD peritonitis, i.e., Staphylococcus epidermidis, S. aureus, E. coli, and Pseudomonas aeruginosa, have been studied in vitro to determine their growth capabilities and survival in peritoneal dialysis fluids (86,126,145). Verbrugh and colleagues found that staphylococci could not survive in commercially prepared dialysis solutions but grew well in the peritoneal dialysis effluents recovered from patients after the dwell time (postdialysis fluid).…”
Section: Portals Of Entry and Microbial Pathogenicity Factorsmentioning
confidence: 99%
“…On the basis of their findings, Sheth et al reasoned that culture-negative cases of peritonitis were probably due to gram-positive cocci, especially coagulase-negative staphylococci, since these organisms may not be readily culturable because of their poor survival in peritoneal fluid (126). The viability of S. epidermidis in commercial dialysis fluids fortified with 0.5 to 4.25% glucose was studied by MacDonald and coworkers (86). They found that fresh dialysis fluid (of all osmolarities tested) neither supported the growth of S. epidermidis nor was bactericidal.…”
Section: Portals Of Entry and Microbial Pathogenicity Factorsmentioning
confidence: 99%